Perceptions of the Graduating BEED Students in Teenage Pregnancy in the Philippines and its Effect to Education: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Philippines has increasing numbers of teenage pregnancy. Through this pandemic, the cases of teenage pregnancy are also increasing because of some factors. Teenage Pregnancies often results in single parenthood, which catalyzes conditions that render the mothers irresponsible. This study employed the descriptive method design to investigate and collect information. To gather data, researchers used a survey questionnaire using Google Forms. The respondents were composed of thirty students of Bachelor of Elementary Education. In choosing the respondents, the researchers used a simple random sampling design.